Experimental Harmonics Analysis of UPS (Uninterrupted Power Supply) System and Mitigation Using Single-Phase Half-Bridge HAPF (Hybrid Active Power Filter) Based on Novel Fuzzy Logic Current Controller (FLCC) for Reference Current Extraction (RCE) - Mahendar Kumar; M.A Uqaili; Z.A Memon; Bhagwan Das (Advances in Fuzzy Systems)
UPS Uninterruptible power supply) is used as backup when the input source, usually the national grid, fails to give power to a load. In addition to the growing use of electronic power devices in industrial and residential systems, such as UPS, controlled rectifiers, SMPS (Switch Mode Power Supplies), and DC Converters, there is a serious problem caused by harmonics in AC mains, which lowers the power quality. Harmonics can cause a variety of problems, including sensitive equipment failure, resonance issues, heated wires, power loss, and inefficient distribution systems. A passive or active power filter could be used to reduce harmonics. However, passive filters are more difficult to design and are bulkier. With the advancement of power electronics, active power filters were developed, and the best combination of both was supplied in the form of hybrid active power filters (HAPF). This study shows an approach to minimizing the harmonics contained in the output of a UPS connected to a nonlinear load. Experiments with several UPS types have been conducted under various nonlinear loads, as well as charging and discharging of batteries, and the proposed technique significantly reduces harmonics in a system with a HAPFs (hybrid active power filter) based on a unique FLCC (fuzzy logic current controller). In this paper, we use a fuzzy logic controller to generate pulse width modulation (PWM) switching signals in a single-phase half-bridge HAPF. The operation of the proposed PWM-FLCC will be studied in a steady and transient state. Based on a connection between the uninterrupted power supply (UPS) supplying a single-phase power to a nonlinear load, different power filter topologies and a brief review of reference current extraction (RCE) methods used in this study were also included and the most common configurations have been compared with their advantages and disadvantages to ensure the right selection of the power filter for UPS connected with the nonlinear load. The results of the investigation demonstrate that the HAPF with the fuzzy logic current controller has reasonable performance, with a significant reduction in current THD down to 1.09%, as per IEEE-519 standard.